2022
DOI: 10.1021/acsanm.2c03382
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride Nanotubes Modified on a Lead-Free Solder Alloy for Microelectromechanical Packaging

Abstract: In this study, we have investigated the role of boron nitride nanotubes (BNNTs) on the microstructural and interconnection reliability of a Sn–3.0 wt % Ag–0.5 wt % Cu (SAC305) lead-free solder alloy for microelectromechanical (MEMS) packaging. The BNNT was added in different fractions (0, 0.03, 0.1, 0.2, 0.4, and 0.6 wt %) to a SAC305 molten bath by manual mixing and melting to fabricate a BNNT-decorated SAC305 alloy (B-SAC). We evaluated the effects of BNNTs on the grain morphology, intermetallic compound (IM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Numerous studies have been conducted to address the aforementioned issues, including grain size control, enhancing yield strength, ductility, and tensile strengths, through metallic additions like Ag, Cu, Ni, In, Al, Sb, Ti, etc., or nonreactive NPs (graphene, carbon nanotubes, carbon nanofibers, boron nitride nanotubes, Al 2 O 3 , TiO 2 , ZrO 2 , SiC, ZrSiO 4 , etc.) to solder matrices. , Previous works by Sharma et al have shown that the addition of NPs to solder matrices effectively decreases the IMCs as well as refines the harder Bi phases in the Sn–Bi matrix . Similar claims have been made by previous reports on solder wettability, electromigration, anticorrosion property, and minimum coarsening of brittle IMCs phases over time. , Nanotubes of carbon and boron nitrides are attractive but there are severe issues of NPs segregation in the solder melt. , Nanodispersed conducive adhesives have also been used as interconnecting materials to improve thermal stability and impact strengths.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Numerous studies have been conducted to address the aforementioned issues, including grain size control, enhancing yield strength, ductility, and tensile strengths, through metallic additions like Ag, Cu, Ni, In, Al, Sb, Ti, etc., or nonreactive NPs (graphene, carbon nanotubes, carbon nanofibers, boron nitride nanotubes, Al 2 O 3 , TiO 2 , ZrO 2 , SiC, ZrSiO 4 , etc.) to solder matrices. , Previous works by Sharma et al have shown that the addition of NPs to solder matrices effectively decreases the IMCs as well as refines the harder Bi phases in the Sn–Bi matrix . Similar claims have been made by previous reports on solder wettability, electromigration, anticorrosion property, and minimum coarsening of brittle IMCs phases over time. , Nanotubes of carbon and boron nitrides are attractive but there are severe issues of NPs segregation in the solder melt. , Nanodispersed conducive adhesives have also been used as interconnecting materials to improve thermal stability and impact strengths.…”
Section: Introductionmentioning
confidence: 63%
“…2,9,11,29,36 The shear fractured surfaces are also presented to compare the microstructural features after shear tests (Figure 8g In general, it is understood that shear strength declines at higher NPs concentrations (x > 0.6). 2,9,11,29,36 Therefore, the reflow at elevated temperatures causes the development of Cu−Sn type IMC at the interface, which affects the shear strength value (Figure 8l). The shear-cracked solder joints shown in Figure 8g−k show that a combination of big shear dimples is observed in pristine Sn−Ni/Cu joints.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of NO by CO is a structure-sensitive reaction, where CO removes oxygen from the NO molecule to form N 2 . In this process, the reactant gases NO and CO must be efficiently adsorbed on the catalytic reaction site to undergo dissociation and successive conversion reaction. , Because BNNT is a highly inert material with a wide band gap, creating defects and vacancies on its surface through oxidation of the B–N bond leads to a decrease in the band gap and also improves the attachment of metal nanoparticles to its surface, thereby enhancing its catalytic properties . The vacancies and defects on the f-BNNT surface caused as a result of the hydroxylation process play a dual role in the catalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, e --h + diffusion continues until the EF is reached, leading to an internal electric field at the interface, and the e --h + accumulation layers across Sb/G [64]. When the Sb/G sensor was exposed to air, O2 gas species easily adsorbed on the surface of the Sb/G and captured es to form chemisorbed O2 species at the interface according to equations ( 9) and (10).…”
Section: Discussion On Sensing Mechanismmentioning
confidence: 99%
“…Organic polymer-based sensors have also shown notable gas response, but undergo adverse polymerization reactions under gaseous atmosphere [9]. MOX-based sensors are the most promising because of their low power requirements, portable structures, cost-effective fabrication, and high compatibility with wafer level microelectronic packaging [10][11][12][13]. However, their sensing mechanism relies on their energy states after adsorption and exhibits poor selective response amongst wide variety of interfering gases.…”
Section: Introductionmentioning
confidence: 99%